OPTIMALISASI LAHAN PEKARANGAN DI DESA PANDEYAN, GROGOL, SUKOHARJO - Joko Sutrisno; Eddyt Triharyanto (Universitas Sebelas Maret, 2018)
Grogol sub-district is one of the subdistricts in Sukoharjo, Central Java, which has transformed rice fields into settlements, companies and other uses. One of the existing residential areas in Grogol District is Pandeyan housing. The area of the yard that can be used for planting area only slightly while the price of food crops are more expensive. The narrow garden optimization is necessary in this regard. Hydroponics and vertikultur is a method of planting without soil and small garden yard. So far, Grogol sub-district housewives have not maximized the utilization of their home yards due to the limited knowledge of farming methods. Therefore, assistance is needed to introduce narrow gardening techniques in residential areas, especially in Pandeyan Housing to PKK group mothers. It aims to increase the productivity of the existing yard area. Methods used to help overcome the above problems include: business management training, training and partial support of appropriate technology support, and assistance.